GAMBARAN PENGETAHUAN IBU TERHADAP PELAKSANAAN IMUNISASI CAMPAK DI PUSKESMAS BAYAN - Fetty Chandra Wulandari; Anes Lucsyana Susilo (Jurnal Komunikasi Kesehatan, 2022)
In 1996 it was concluded that measles was possible to be medicated, because the only host orreservoir of measles was only humans and the existence of a vaccine with a high enoughpotency with a vaccine efficacy of 85%. Based on the recording and reporting in Indonesia in2016, the measles immunization coverage was 92.5%. And there were problems at the BayanHealth Center. 30 (23.43%) people did not know about measles immunization. The purpose ofthe study was to describe the mother's knowledge of the implementation of measlesimmunization at the Bayan Health Center. This type of research is descriptive, the researchmethod uses a cross sectional approach, the population is all mothers who have babies aged0-9 months, a sample of 20 people, the sampling method is accidental sampling, the datacollection technique uses a questionnaire, the research analysis uses univariate analysis, thevalidity test uses the Pearson product. moment and reliability test using alpha cronbach andprogram data using SPSS 16. The results showed the majority of respondents were >30 yearsold (45%), high school education (65%), not working (75%), and the majority of respondentshad knowledge of immunization measles category enough (55%).